Clinical Impact of Cervical Imbalance on Surgical Outcomes of Laminoplasty: A Propensity Score–Matching Analysis. Issue 1 (February 2020) - Tamai, Koji; Suzuki, Akinobu; Yabu, Akito; Terai, Hidetomi; Hoshino, Masatoshi; Toyoda, Hiromitsu; Takahashi, Shinji; Ohyama, Shoichiro; Hori, Yusuke; Nakamura, Hiroaki
Abstract : Study Design: This is a retrospective cohort study. Objective: The objective of this study was to identify the impact of preoperative cervical sagittal balance on the 2-year surgical outcomes of laminoplasty. Summary of Background Data: The cervical imbalance is considered associated with poor health-related quality of life and poor outcomes for cervical deformity surgery. However, the influences of cervical imbalance on the clinical outcomes of laminoplasty for cervical spondylotic myelopathy (CSM) patients are unclear. Materials and Methods: A total of 277 consecutive CSM patients who underwent laminoplasty were analyzed. From the last consecutive 136 patients, matched control group [cervical sagittal vertical axis (cSVA)<40 mm, n=30] and matched imbalance group (≥40 mm, n=30) were selected based on their propensity score adjusted for age, sex, cervical alignment, and preoperative Japanese Orthopaedic Association (JOA) score. Change in clinical outcomes and radiographic parameters at 2 years postoperatively were compared between the 2 matched groups using mixed-effects model. For the validation of the primary results, factors that correlated with the recovery rate of JOA score of another 141 patients were analyzed using multiple linear regression analysis. Results: There was no significant interaction between the 2 matched groups in all clinical outcomes, including the severity of myelopathy, patient-oriented health-related quality of life score, physical and mental status, physical functions, and pain score. Regarding the radiographic evaluation, change in cSVA showed significant differences ( P =0.038); cSVA was kept stable in the matched control group, whereas its value significantly decreased in the matched imbalance group. Multiple linear regression models demonstrated that preoperative cSVA is not significantly related to the recovery rate of JOA score at 2 years postoperatively ( P =0.114). Conclusions: Preoperative cervical imbalance did not significantly affect the 2-year surgical outcomes of laminoplasty. Furthermore, cervical imbalance improved after surgery. These results can suggest physicians consider laminoplasty as a treatment for CSM patients regardless of their cervical balance. Level of Evidence: Level III—treatment benefits: nonrandomized controlled cohort/follow-up study.